Forced Displacement and Sovereignty: Legal Challenges and Accountability Under International Criminal Law - Belal AbuHasballah (CV. Era Digital Nusantara, 2025)
Abstract: This article examines forced displacement and eviction as crimes under international criminal law. It explores how international legal frameworks, including the Rome Statute and the Geneva Conventions, define and criminalize these acts, while also analyzing the challenges in enforcement due to political and jurisdictional limitations. The study highlights the case of forced displacement in Gaza as a concrete example of how such acts violate international humanitarian law and expose the weaknesses of international legal mechanisms in ensuring accountability. Purpose: The study aims to analyze the legal framework governing forced displacement under international law, assess the challenges in prosecuting perpetrators, and propose ways to strengthen enforcement mechanisms. Design/Methodology/Approach: This research employs a descriptive-analytical approach by examining legal texts, international agreements, court rulings, and academic literature. It also analyzes case studies, particularly focusing on Israel’s forced displacement of Palestinians in Gaza, to illustrate the legal, political, and humanitarian implications. Findings: The study finds that while international law clearly defines forced displacement as a crime, enforcement remains selective and politically influenced. The research underscores the limitations of international legal bodies, such as the ICC, in holding powerful states accountable. It also highlights the need for strengthening universal jurisdiction mechanisms to prevent states from using sovereignty as a shield against accountability. Originality/value: This study contributes to the discourse on state sovereignty and international criminal law by critically examining the legal gaps in addressing forced displacement. It provides new insights into how international legal frameworks can be reinforced to ensure greater accountability for human rights violations.